THE CHANGES IN SEED QUALITY OF SELECTED PEPPER VARIETIES IN THREE YEARS - Zivkovic, Ivana (Journal on Processing and Energy in Agriculture, 2022)
Pepper (Capsicum annuum L.) as a commercial species includes a large number of different varieties and is one of the most popular vegetables around the world. Changes in the quality of the seeds of autochthonous varieties of pepper seeds: Palanačko Čudo, Župska Rana, and Kobra were monitored in three years (2019–2021). It was noticed that the slightest difference in germination was obtained with the cultivar Palnačko Čudo (p>0.05) in three years. The parish wound had the best germination in 2019 (95%) compared to Palnačko Čudo and Kobra (p<0.05). The germination energy of Župska Rana is significantly higher compared to other selected varieties, 89% (p<0.05). There was a significant decrease in total germination in 2020 compared to 2019 (p<0.05) and amounted to 83%; accordingly, the germination energy decreased. No phytopathogenic fungi were detected in the Župska Rana sample. Total germination and energy decreased significantly compared to the previous two years (p<0.05). During the analysis of quality parameters in 2021, the slightest change in quality was observed in the variety Palanačko Čudo, including germination energy and moisture. A significant decrease in the germination of Župska Rana was noticed during the period 2019–2021. The lowest percentage of phytopathogenic fungi in the three years was detected in Župska Rana.